Implementasi Proyek Penguatan Profil Pelajar Pancasila Untuk Meningkatkan Kreativitas Peserta Didik Kelas IV SDN 10 Bandar Buat - Wahyuni, Aprilla; Muhammadi, Muhammadi (Universitas Negeri Padang, 2024)
Project-based learning in elementary schools is still rarely carried out and learning does not yet provide opportunities for students to collaborate in order to achieve goals well. The solution to overcome this requires a comprehensive understanding of the project. This study was conducted to explain the implementation of the Strengthening Student Pancasila Profile Project (P5) with the theme of Entrepreneurship at SDN 10 Bandar Buat. This research adopts a descriptive qualitative approach. It utilises two types of data: primary data and secondary data. Primary data were obtained through interviews with the School Principal, P5 Coordinator, and Grade IV Teachers, as well as observations. Secondary data were obtained through documentation studies and field notes. The results of this research indicate that the implementation of P5 with the theme of Entrepreneurship at SDN 10 Bandar Buat runs smoothly and receives positive responses from students. P5 activities are able to enhance entrepreneurial spirit and cooperation among students, as well as increase creativity. However, it needs improvement in terms of duration to make the entrepreneurial experience for students more meaningful.